1995
DOI: 10.1007/bf00448952
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with oral cefadroxil versus intravenous cefuroxime in trochanteric fracture surgery

Abstract: A prospective, randomized study was performed in 559 patients to compare two doses of oral cefadroxil with three doses of intravenous cefuorxime as antibiotic prophylaxis in intra- and subtrochanteric hip fracture surgery. Antibiotic concentrations in the wound fluid were determined at the start and at the end of the operation. The first dose of cefadroxil was given about 2 h before surgery and cefuroxime about 30 min before operation. In 226/242 (93%) patients randomized to oral cefadroxil, the concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Investigations from various surgeries have demonstrated that oral antibiotic prophylaxis is effective for preventing infectious complications [15,16,[36][37][38]. Moreover, the oral route of prophylaxis is likely to be more appropriate for day-case hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations from various surgeries have demonstrated that oral antibiotic prophylaxis is effective for preventing infectious complications [15,16,[36][37][38]. Moreover, the oral route of prophylaxis is likely to be more appropriate for day-case hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…The empirically selected antibiotic agent was cephadroxil as it has a better range compared to cephalexin, with a better action against strains of Staphylococcus and Streptococcus, as well as exhibiting a good penetration into bone tissue [21]. Specific antibiotic therapy, on the other hand, is limited to subsequent stages, according to the results of cultures.…”
Section: Commentsmentioning
confidence: 99%
“…Even though, in our service, daily assessment of surgical wounds was already routinely performed, the new protocol established a stricter sampling of wound secretions for culturing and an earlier start to antibiotic therapy. The empirically selected antibiotic agent was cephadroxil as it has a better range compared to cephalexin, with a better action against strains of Staphylococcus and Streptococcus, as well as exhibiting a good penetration into bone tissue [21]. Specific antibiotic therapy, on the other hand, is limited to subsequent stages, according to the results of cultures.…”
Section: Commentsmentioning
confidence: 99%